2018
DOI: 10.1007/s10661-018-6501-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of fluoride on clinical and subclinical indices of fluorosis in school going children and its mitigation by supply of safe drinking water for 5 years: an Indian study

Abstract: Fluorosis is a public health problem in India; to know its prevalence and severity along with its mitigation measures is very important. The present study has been undertaken with the aim to assess the F dose-dependent clinical and subclinical symptoms of fluorosis and reversal of the disease by providing safe drinking water. For this purpose, a cross-sectional study was undertaken in 1934 schoolgoing children, Nalgonda district. Study villages were categorized into control (category I, F = 0.87 mg/L), affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Clinically, elevated TSH levels often correlate with reduced T3 and T4 production, indicating a response to hormone deficiency and a need for increased production and release. This pattern was observed in studies by Khandare, Validandi [ 23 ] and [ 24 , 25 ], although [ 22 ] reported no such correlation. Moreover, while an increase in PTH is relevant, it does not directly influence thyroid functions.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Clinically, elevated TSH levels often correlate with reduced T3 and T4 production, indicating a response to hormone deficiency and a need for increased production and release. This pattern was observed in studies by Khandare, Validandi [ 23 ] and [ 24 , 25 ], although [ 22 ] reported no such correlation. Moreover, while an increase in PTH is relevant, it does not directly influence thyroid functions.…”
Section: Discussionsupporting
confidence: 63%
“…The studies did not categorize participants according to life stages, such as childhood, adolescence, adulthood, middle age, or senior years. Wang, Wang [ 22 ], Kutlucan, Koroglu [ 15 ], Khandare, Validandi [ 23 ], Zulfiqar, Rehman [ 24 ] and Zulfiqar, Ajaz [ 25 ] evaluated participants ranging in age from 7 to 18 years. Conversely, Leone, Leatherwood [ 20 ] focused on adult and older individuals, with ages ranging from 18 to 60 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of fluoride in drinking water can cause an increase in TSH concentrations [ 59 ]. Higher levels of fluoride in urine and levels of TSH have also been observed in children and teenagers from areas with endemic fluorosis [ 86 , 87 ]. Our findings are in line with those published by Kheradpisheh et al [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride exposure during early brain development has been associated with diminished intelligence quotient (IQ) scores among children living in areas with high levels of naturally occurring fluoride in drinking water (~3 mg/L) [ 1 , 2 , 3 ] and in areas where fluoride is added to public water supplies or salt for caries prevention [ 4 , 5 , 6 ]. The mechanism(s) underlying fluoride-associated cognitive deficits are not well understood, but changes to the thyroid function may be one such mechanism [ 7 , 8 , 9 , 10 , 11 ]. In 2006, the National Research Council (NRC) classified fluoride as an endocrine disruptor and recommended more research to understand fluoride’s effects on the thyroid gland, especially in iodine deficient pregnant women [ 12 ].…”
Section: Introductionmentioning
confidence: 99%